Instrument processing: knowledge and practice among manicurists/pedicurists - Juliana Ladeira Garbaccio; Adriana Cristina Oliveira; Amanda Laís Gonçalves Gama (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
Objective: to evaluate the knowledge and practices of instrument processing by manicurists/pedicurists in beauty salons in the city of Belo Horizonte, Brazil. Method: This was a survey-type cross-sectional research with manicurists/pedicurists, between June 2012 and March 2013 in 235 beauty salons in Brazil. The answers were categorized using the Statistical Package for the Social Sciences, by means of descriptive statistics, Pearson's Chi-Squared or Fisher's exact tests, and multivariate binary logistic regression, to analyze the influence of sociodemographic variables. Results: The majority (68.1%) correctly defined sterilization; however, the adherence to moist heat (autoclave) was low (35.3%). The temperature and the exposure time to sterilization methods varied, with the majority (44.7%) citing a minimum of 200°C for 60 to 90 minutes (32.8%). The respondents reported reusing disposable instruments with their customers, but pointed out individual use of instruments as the correct procedure (90.6%). Conclusion: Despite their knowledge, professionals practice was inappropriate regarding instrument processing, which can place their own health and that of their customers at risk.